PENERAPAN MASSAGE MULAI DARI BAHU SAMPAI KEPALA TERHADAP NYERI KEPALA PADA PASIEN HIPERTENSI DI RUMAH SAKIT TK III 04.06.02 BHAKTI WIRA TAMTAMA SEMARANG - Ainnur Rahmanti; Tolcha Ami N (Jurnal Kesehatan Medika Udayana, 2021)
Hypertension is a chronic condition that results in an increase in blood pressure. Hypertension can cause headaches, headache is pain in the head that causes discomfort. One way to overcome them is by massage. The purpose of this case study is to describe the application of massage from shoulder to head to the level of headache in hypertensive patients. The method used is descriptive research. This research was conducted on 2 subjects. The subjects of this study were hypertension patients with criteria of being willing to be respondents, stage 1 hypertension with mild headaches, age 40 years and above. Analysis of the level of headache was done descriptively and measured based on the Numeric Rating Scale. The results of the analysis showed a decrease in the level of headache after the intervention. In subject I mild headache with a scale of 3 to scale 1 and subject II of mild headache with a scale of 3 became a scale 1. Conclusion that massage from the shoulder to the head is effective for reducing headaches, especially in hypertensive patients who experience headaches. Recommendations for nurses can apply massage therapy to reduce the level of headache in hypertensive patients